2013
DOI: 10.1016/j.earlhumdev.2013.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Regular breakfast consumption is associated with increased IQ in kindergarten children

Abstract: Background Studies have documented a positive relationship between regular breakfast consumption and cognitive outcomes in youth. However, most of these studies have emphasized specific measures of cognition rather than cognitive performance as a broad construct (e.g., IQ test scores) and been limited to Western samples of school-age children and adolescents. This study aims to extend the literature on breakfast consumption and cognition by examining these constructs in a sample of Chinese kindergarten-age chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 63 publications
5
45
0
Order By: Relevance
“…Although there was no association between the analyzed factors and non-adherence to the consumption of morning snacks, the low adherence is worrisome, since breakfast is an important meal, which when frequently eaten is related to better cognitive performance [17], in accordance with the recommendations of the PNAE [3]. A considerable proportion of the students justified their reason for not having this meal at school as they having had breakfast at home, but this practice was not investigated.…”
Section: Discussionmentioning
confidence: 95%
“…Although there was no association between the analyzed factors and non-adherence to the consumption of morning snacks, the low adherence is worrisome, since breakfast is an important meal, which when frequently eaten is related to better cognitive performance [17], in accordance with the recommendations of the PNAE [3]. A considerable proportion of the students justified their reason for not having this meal at school as they having had breakfast at home, but this practice was not investigated.…”
Section: Discussionmentioning
confidence: 95%
“…A cross-sectional study consisted of a sample of 1269 children (697 boys and 572 girls) aged 6 years from the Chinese city of Jintan. Findings showed that children who regularly have breakfast on a near-daily basis had significantly higher full scale, verbal, and performance IQ test scores (all pb 0.001) compared to children who "sometimes" have breakfast (Liu et al, 2013). Recently in Japan, elementary school children who had sleep hours gen erally longer than 9 hours showed clearly higher markings in Japanese language than those who had slept only less than 9 hours (Takeuchi et al, 2017).…”
Section: Breakfast and Academic Achievement In Schoolsmentioning
confidence: 95%
“…Measurements of HBC are normally unvalidated brief dietary assessments, such as questionnaires with one item to assess breakfast intake frequency (e.g., How often do you consume breakfast per week?) (28), which may yield an inadequate assessment of habitual intake. Often, participants are not given a clear definition of breakfast, meaning that breakfast was subjectively interpreted by the individual (26, 28).…”
Section: Breakfast and Cognitive Performancementioning
confidence: 99%